Relationship between Knowledge Level and Anxiety in Premenopausal Women - Yuniawati Astuti; Alfian (Unit Penelitian dan Pengabdian Masyarakat STIKES Fatmawati Jakarta, 2024)
Before menopause, a woman will experience premenopause, which is the beginning of biological, physiological changes and other clinical symptoms as the beginning of menopause and includes one year or the first twelve months after menopause. Physical changes due to decreased estrogen and progesterone production cause various symptoms, both related to reproductive organs and other body organs. Changes that occur during menopause also affect a woman's psychological state. The purpose of this study was to determine the relationship between the level of knowledge and anxiety in women approaching menopause at Posyandu Melati II, Jatibening Village. This study was quantitative with a cross-sectional design that aimed to determine the relationship between the level of knowledge and anxiety in premenopausal women. The sample in this study were women aged over 40 years and had not yet experienced menopause at Posyandu Melati II, Jatibening Village in 2018, Bekasi, obtained through total sampling. Of the 40 respondents, it was found that respondents with low knowledge experienced the most anxiety, as many as 13 people (46.4%). Respondents with high knowledge did not experience anxiety, as many as 1 person (8.3%). The data obtained indicates a relationship between knowledge and anxiety. Women at the Melati II Integrated Health Post (Posyandu) in Jatibening Village who are in premenopause need to gain more information about the signs and symptoms of menopause from reliable sources to help them navigate menopause effectively and without anxiety.